Situation Report: Romania, 17 August 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Aspects of the Cultural Campaign Political and Ideological Instruction in Educational Institutions Karl Schiller Visits Romania Bumper Wheat Yield Reaction to Comecon Integration Program (I) Local Party Meetings Discuss Ideological Campaign